Antihypertensive and Antioxidant Potential of Purple Sweet Potato Tuber Dry Extract in Hypertensive Rats - Jawi, I Made; Sutirta-Yasa, I. W. P.; Mahendra, Agung Nova (BALI MEDICAL JOURNAL, 2016)
Background: Purple sweet potato tuber extract in liquid form, shown to lower blood pressure of hypertensive rats and hypertensive patients. Liquid dosage form, increasingly unstable when stored for long periods, thus it is necessary to find a more stable dosage form. The objective of this research was to prove that dry extract of purple sweet potato tuber has the same effects with liquid extract in hypertensive rats. Method: The is a randomized pre-test and post-test control group design study. Thirty hypertensive model rats were divided into 5 groups (6 animals for each group). Group 1 was treated as a control group. Group 2 to group 5 were treated as treatment groups. Treatment groups were given liquid extract at a dose of 3 ml, dry extract with the dose of 200 mg, dry extract that stored in a certain time with a dose of 200 mg and given a mixture of dry extract with a carrier substance (capsule formula) with a dose of 200 mg, respectively, for 4 weeks. Variables observed were blood pressure, SOD and MDA level of the blood. Results: The results showed that the group given the purple sweet potato tuber extract lowers blood pressure were significantly in liquid extract or dry extract (p <0.01). The group that was treated with capsule formula showed more decrease in blood pressure than dry extract group (p <0.01). The similar results happened on MDA and SOD level in blood. Conclusions: Thus, it can be concluded that dried extract of purple sweet potato tubers has the same effectiveness with liquid extract, both as an antihypertensive and also antioxidant. Capsules formula is more effective than liquid extract and dry extract.